The Implementation of Science, Technology, Engineer, Math (STEM) in English Language Learning at SMA N 1 Boja - Linda Yuana; Sri Wuli Fitriyati; Suwandi Suwandi (English Education Journal, 2022)
STEM (Science, Technology, Engineering, Math) is an approach in a learning process which integrated Science, Technology, Engineer and Mathematics in one circle students’ learning experience. This integration means to let students learn from the real problems emerged in their real life and become a problem solver by using their knowledge. The choice of appropriate approach can help teachers to optimize their teaching objectives. An approach is a way of looking at teaching and learning. This research focus on STEM as an approach with one disciplinary and interdisciplinary subject. The objectives of this study are to find out how teachers perceive STEM in English Language Teaching, how to implement STEM in classroom practices and how conduct the evaluation of STEM as the whole program. The method used in this research is qualitative case study, in which researcher uses questionnaire, interview and observation as the instrument of research. The result shows that teachers have good perception on STEM. As they belief that STEM can promote students’ critical thinking and problem-solving skills. It gives impact to their planning and also implementing STEM in their classes. Teachers plans the learning activity in form of Problem Learning or Project-based Learning. They also conduct a classroom activities using science-based material. This research also showed the evaluation of STEM implementation through classroom reflection and teachers’ reflection in interdisciplinary subjects.The planning, implementation and evaluation are aligned with teacher’s perception of STEM.